Peran Pendidikan Agama Kristen dalam Memajukan Kerukunan Umat Beragama di Jakarta - Feri Simanjuntak; Nini Adelina Tanamal (Departement of Mathematics Education, 2022)
The motivation for this research is that there are still many people in the Capital Region of Jakarta who believe that education is not important, because they see that many people who have only completed junior high school are on the same level as those who have gone through tertiary education. What is the role of education in maintaining inter-religious tolerance in Jakarta. The study used the interview method in which the researcher went into the field to collect data. The results of this study are very clear: education is essential for improving human life, and it can also help to improve relations between people of different cultures and beliefs, The role of the elite in society is to maintain tolerance by guiding and protecting the community. The role of government in carrying out its duties is very beneficial, namely acting as an umbrella in society in promoting tolerance in Jakarta.